Physical and psychosocial risk factors for musculoskeletal disorders in Brazilian and Italian nurses - Michele Carugno; Angela Cecilia Pesatori; Maurizio Ferrario; Andrea Lepos Ferrari; Fábio José da Silva; Aline Caldas Martins; Vanda Elisa Andrés Felli; David Coggon; Matteo Bonzini (2012)
As part of the international CUPID investigation, we compared physical and psychosocial risk factors for musculoskeletal disorders among nurses in Brazil and Italy. Using questionnaires, we collected information on musculoskeletal disorders and potential risk factors from 751 nurses employed in public hospitals. By fitting countryspecific multiple logistic regression models, we investigated the association of stressful physical activities and psychosocial characteristics with site-specific and multisite pain, and associated sickness absence. We found no clear relationship between low back pain and occupational lifting, but neck and shoulder pain were more common among nurses who reported prolonged work with the arms in an elevated position. After adjustment for potential confounding variables, pain in the low back, neck and shoulder, multisite pain, and sickness absence were all associated with somatizing tendency in both countries. Our findings support a role of somatizing tendency in predisposition to musculoskeletal disorders, acting as an important mediator of the individual response to triggering exposures, such as workload.